Fever under 3 months and the full septic screen: Time to think again? A retrospective cohort study at a tertiary‐level paediatric hospital. (30th October 2017) - Aldridge, Patrick; Rao, Arjun; Sethumadavan, Rebecca; Briggs, Nancy
Abstract : Aim: To assess adherence to the Iocal guideline (LG) for the management of fever in infants under 3 months and whether the application of a risk‐stratified protocol (RSP) to this population would miss any serious bacterial infections (SBI) compared to current practice (CP) and LG. Methods: All presentations to the authors' Emergency Department of infants 0–3 months with fever from 1 July 2015 to 28 April 2016 were included ( n  = 219), along with a detailed analysis of CP. The initial history, examination and pathology results were applied to the LG and RSP to assess what changes in management would occur. The primary end point was a missed SBI, with secondary outcomes measuring the number of invasive procedures performed, antibiotics prescribed and admissions. Results: Adherence to the LG was 83% with three missed SBIs. Strict adherence would have resulted in eight missed SBIs. This indicates that both warranted and unwarranted variation exists in current clinical practice. Application of the RSP showed no missed SBIs but, compared to CP, indicates a statistically significant increase in admissions and full septic screens (admissions 95% vs. 83%, P  < 0.05; full septic screens 82% vs. 72%, P  < 0.05). Chest X‐rays were infrequently requested (10%) and the validity of use in this group warrants further study. Conclusion: An ad hoc risk‐stratified practice already exists at the authors' institution, and application of an RSP did not miss any SBIs. Adoption and implementation of a formal RSP is currently being formulated.